Immune Modulation by Transplanted Calcium Phosphate Biomaterials and Human Mesenchymal Stromal Cells in Bone Regeneration - Humbert, Paul; Brennan, Meadhbh Á.; Davison, Noel; Rosset, Philippe; Trichet, Valérie; Blanchard, Frédéric; Layrolle, Pierre (Frontiers in Immunology, 2019)
A wide variety of biomaterials have been developed as both stabilizing structures for the injured bone and inducers of bone neoformation. They differ in chemical composition, shape, porosity and mechanical properties. The most extensively employed and studied subset of bioceramics are calcium phosphate materials (CaPs). These materials, when transplanted alongside mesenchymal stem cells (MSCs), lead to ectopic (intramuscular and subcutaneous) and orthotopic bone formation in preclinical studies, and effective fracture healing in clinical trials. Human MSC transplantation in pre-clinical and clinical trials reveals very low engraftment in spite of successful clinical outcomes and their therapeutic actions are thought to be primarily through paracrine mechanisms. The beneficial role of transplanted MSC could rely on their strong immunomodulatory effect since, even without long-term engraftment, they have the ability to alter both the innate and adaptive immune response which is critical to facilitate new bone formation. The current knowledge on the immune response to the implantation of CaP biomaterials alone or in combination with MSC is presented. In particular the central role of monocyte-derived cells, both macrophages and osteoclasts, in MSC-CaP mediated bone formation is emphasized. Biomaterial properties, such as macroporosity and surface microstructure dictate the host response and the ultimate bone healing cascade. Understanding intercellular communications throughout the inflammation, its resolution and the bone regeneration phase is crucial to improve the current therapeutic strategies or develop new approaches.